The toileting habit profile questionnaire: Examining construct validity using the Rasch model. (April 2019) - Beaudry-Bellefeuille, Isabelle; Bundy, Anita; Lane, Alison; Ramos Polo, Eduardo; Lane, Shelly J
Introduction: Preliminary reports support the hypothesis that sensory issues may be related to atypical defecation habits in children. Clinical practice in this area is limited by the lack of validated measures. The toileting habit profile questionnaire was designed to address this gap. Methods: This study included two phases of validity testing. In phase 1, we used Rasch analysis of existing data to assess item structural validity, directed content analysis of recent literature to determine the extent to which items capture clinical concerns, and expert review to validate the toileting habit profile questionnaire. Based on phase 1 outcomes, we made adjustments to toileting habit profile questionnaire items. In phase 2, we examined the item structural validity of the revised toileting habit profile questionnaire. Results: Phase 1 resulted in a 17-item questionnaire: 15 items designed to identify habits linked to sensory over-reactivity and two designed to identify sensory under-reactivity and/or poor perception items. The analysis carried out in phase 2 supported the use of the sensory over-reactivity items. Remaining items can be used as clinical observations. Conclusion: Caregiver report of behaviour using the revised toileting habit profile questionnaire appears to adequately capture challenging defecation behaviours related to sensory over-reactivity. Identifying challenging behaviours related to sensory under-reactivity and/or perception issues using exclusively the revised toileting habit profile questionnaire is not recommended.